Diets That Have Potential to Stimulate the Hypothalamic-Pituitary-Adrenal (HPA) Axis in Sprague Dawley Rats - Khairil Azwan; Resni Mona; Jannathul Firdous; Pamela Rosie David; Dina Keumala Sari; Noorzaid Muhammad (Talenta Publisher, 2023)
Background: The pituitary gland is the master gland regulating body hormones. From the anterior pituitary’s corticotrophs, adrenocorticotrophic hormone (ACTH) is secreted and influences corticosterone production in rodents via the hypothalamic–pituitary–adrenal (HPA) axis. ACTH and corticosterone are commonly used as hormonal stress markers. Disturbances in ACTH and corticosterone are seen in diseases like Addison’s disease, Cushing’s syndrome, and metabolic syndrome. Objective: To observe which diet induces the most and least stress on Sprague Dawley rats’ physiology. Methods: Thirty-five Sprague Dawley rats were divided into five groups (n=7) and given different diets (control, high-fat, high-protein, high-sugar, and high-starch) with tap water ad libitum. After eight weeks, blood samples were collected and serum separated. ACTH and corticosterone were extracted, purified, identified, and quantified using High-Performance Liquid Chromatography (HPLC) with photodiode array (PDA) analysis. Results: High-sugar diet led to the highest ACTH blood level. Both high-fat and high-sugar diets showed the highest corticosterone peaks. Conclusion: Consumption of high-fat and high-sugar diets for eight weeks is suggested to induce physiological and metabolic stress in Sprague Dawley rats, as evidenced by HPA axis activation.